Efektivitas Iklan sebagai Komunikasi Pemasaran Berdasarkan Karakteristik Followers Instagram Meatless Kingdom - Hapsari, Hepi; Wulandari, Eliana; Karyani, Tuti; Azzahra, Sheila Najwa (Universitas Galuh, 2026)
Social media, particularly Instagram, has become one of the most widely used promotional channels by businesses, including Meatless Kingdom, a plant-based food brand. This study aims to examine the effectiveness of the advertisements published on Instagram, specifically in attracting the attention and interest of followers and encouraging their purchasing decisions. The effectiveness of the advertisements is assessed using the AIDA model (Attention, Interest, Desire, Action), and is analyzed in relation to the characteristics of the @meatlesskingdom Instagram followers, such as age, gender, education, occupation, and income. Based on a survey of 100 randomly selected followers, the analysis shows that there is no significant relationship between follower characteristics and how they respond to the advertisements. This suggests that the content created by Meatless Kingdom is still too general and has not been specifically directed at its intended target audience—namely, housewives and office workers. In contrast, the majority of the brand’s Instagram followers come from younger age groups with limited purchasing power. These findings provide valuable insights for the company to adjust its future promotional strategies. There is a need to remap the audience and explore other channels or approaches that better match the actual target market, ensuring that promotional messages are not only delivered, but also effective in generating interest and driving purchases.